Psychophysiological evaluation of the Smartick method in children with reading and mathematical difficulties - Corona-González, César E.; Ramos-Flores, Moramay; Alonso-Valerdi, Luz María; Ibarra-Zarate, David I.; Issa-Garcia, Victor (Frontiers in Human Neuroscience, 2024)
Introduction: Assistive technologies for learning are aimed at promoting academic skills, such as reading and mathematics. These technologies mainly embrace mobile and web apps addressed to children with learning difficulties. Nevertheless, most applications lack pedagogical foundation. Additionally, the task of selecting suitable technology for educational purposes becomes challenging. Hence, this protocol posits the psychophysiological assessment of an online method for learning (OML) named Smartick. This platform comprises reading and math activities for learning training. In this protocol, individual monitoring of each child is proposed to determine the progress in learning caused by Smartick.One hundred and twelve children aged between 8 and 12 who present reading or math difficulty after a rigorous psychometric evaluation will be recruited. The study comprises four sessions. In sessions 1 and 2, collective and individual psychometric evaluations will be performed, respectively. Reading and mathematical proficiency will be assessed, as well as attentional levels and intellectual quotient. Subsequently, each child will be semi-randomly assigned to either the experimental or control groups. Afterwards, a first EEG will be collected for all children in session 3. Then, experimental groups will use Smartick for three months, in addition to their traditional learning method. In contrast, control groups will only continue with their traditional learning method. Finally, session 4 will consist of performing a second psychometric evaluation and another EEG, so that psychophysiological parameters can be encountered that indicate learning improvements due to the OML, regardless of the traditional learning method at hand. Discussion: Currently, few studies have validated learning improvement due to assistive technologies for learning. However, this proposal presents a psychophysiological evaluation addressed to children with reading or math difficulties who will be trained with an OML. Ethics committee registration number: This protocol has been registered in BioMed Central with the following number: ISRCTN14013636. Additionally, the Ethics Committee from the Neuroscience Institute of the University of Guadalajara approved this protocol on April 28, 2023, under this number: ET122022-356.1.